KAJIAN ESTETIKA LUKISAN REALIS KONTEMPORER Drs. Irwan, M.Sn. YANG BERJUDUL DI UJUNG TANDUK - Asra Ilal Khairi; Abdul Hafiz (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2022)
Aesthetics was a science that studies things related to beauty, the perspective of beautifulness cannot be the same, some people may be seen something beautiful but not for the others, something that was unstable depends on conditions and situations, therefore beauty is a theory of relativity in which it relates to subjects, objects and value. Talking about aesthetics, it would be related to various disciplines, one of these disciplines was fine arts, in which there were various fields such as painting, graphics, crafts and many other fields of art. Various expressions about the culture began to be expressed by artists in the archipelago, this thing related to the erosion of culture and traditions inherent in society, one of which is through the painting